Holistic Spiritual Care Practices, Competencies, and Needs in Cancer Treatment in Sub-Saharan Africa: A Scoping Review - Gedfew, Mihretie (Journal of religion and health, 2025)
This scoping review critically examines the impact of spiritual care interventions on cancer patients in sub-Saharan Africa, with particular attention to the cultural and contextual factors that influence the delivery of care. Spiritual care is integral to fostering holistic healthcare, particularly in oncology settings where the emotional, psychological, and spiritual needs of patients are paramount. Consequently, the primary objective of this scoping review was to systematically map and delineate the effects of spiritual care on cancer patients across sub-Saharan Africa. A comprehensive search of relevant electronic databases was conducted to identify studies focusing on spiritual care interventions for cancer patients in this region. Data extraction involved a meticulous analysis of study characteristics, including the populations studied, the nature of the interventions, and the outcomes reported. The synthesis of the data entailed categorizing the interventions and evaluating their effectiveness based on the reported outcomes. The review synthesized findings from sixteen studies, which revealed a broad spectrum of spiritual care approaches, encompassing both traditional healing practices and structured interventions facilitated by healthcare professionals. Notably, significant positive outcomes were observed, including improvements in quality of life, enhanced coping strategies, and heightened spiritual well-being among patients who received spiritual care interventions. This scoping review highlights the critical role of culturally attuned spiritual care interventions in improving the overall well-being of cancer patients in sub-Saharan Africa. The findings underscore the need for further research aimed at integrating spiritual care into comprehensive cancer care programs that are specifically tailored to the unique cultural and contextual needs of the region. The review calls for a concerted effort to embed these interventions within the broader framework of cancer care in sub-Saharan Africa to optimize patient outcomes and provide holistic support.